2022
DOI: 10.5296/jbls.v14i1.20181
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Phytoplankton and Water Quality of Some Rivers of Haute Sanaga Department (Central Africa)

Abstract: In Cameroon, rivers are subjected to physicochemical disturbances, which increase the degradation of water quality. The aim of this study was to determine the spatio-temporal diversity of the phytoplankton groups and to evaluate the environmental parameters of the sampling sites in order to assess the quality of water in two hydrographic networks. Physicochemicals analyzes were carried out according to the standard methods while phytoplankton organisms were harvested by direct sampling and analyzed by the Uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Microcystis aeruginosa accounted for higher relative abundance in April, June, July, and August (Table 3), possibly due to their high tolerance for increased temperature and availability of adequate nutrients. In addition, due to their competitive nature, they produce cyanotoxins which exerts allelopathic effects on other phytoplankton and eradicate their predators like the zooplankton (Pascale et al, 2022), thus making them abundant, as observed in this study. Microcystis aeruginosa is a primary cause of the hazardous cyanobacterial bloom that is common around the world and affects freshwater systems (Yang & Wang, 2019).…”
Section: Abundance and Distributionmentioning
confidence: 53%
“…Microcystis aeruginosa accounted for higher relative abundance in April, June, July, and August (Table 3), possibly due to their high tolerance for increased temperature and availability of adequate nutrients. In addition, due to their competitive nature, they produce cyanotoxins which exerts allelopathic effects on other phytoplankton and eradicate their predators like the zooplankton (Pascale et al, 2022), thus making them abundant, as observed in this study. Microcystis aeruginosa is a primary cause of the hazardous cyanobacterial bloom that is common around the world and affects freshwater systems (Yang & Wang, 2019).…”
Section: Abundance and Distributionmentioning
confidence: 53%
“…In West Africa’s Niger River system, Ezewudo et al ( 2021 ) noted weak to high potential ecological risks to aquatic communities, including microalgae, from As, Cd and Hg contamination. In the Cameroon Centre Region, the spatial-seasonal changes in algal densities in the streams of the Sanaga lotic system network draining urban and industrial settlements corresponded to changes in the aquatic physicochemical environment (Pascale 2023 ). According to Mangadze et al ( 2019a ), several ecological health studies on southern Africa’s rivers have applied benthic diatoms for biomonitoring.…”
Section: Introductionmentioning
confidence: 99%